The Resistance of Adivasi Adhikar Samiti (AAS) Againts Forest Development Corporation (FDC) in Chhattisgarh India - Bella Yulidiningrum; Pra Adi Soelistijono (Journal of Feminism and Gender Studies, 2023)
Chhattisgarh is a state in India which separated from the state of Madhya Pradesh in 2000. One part of Chhattisgarh is Koriya District which is located in the northwest corner. The district is one of the most densely forested areas in Chhattisgarh. The prevalence of deforestation and forest conversion is a fundamental problem in India which has caused resistance from various groups in society, especially the Koriya community, who live based on the forest. One of the organizations against illegal logging is Adivasi Adhikar Samiti (AAS), an Indigenous Peoples Rights Organization that focuses on health. Using the concept of eco-feminism, this study will analyze the reasons why AAS plays a role in dealing with the problems of forest conversion and illegal logging in Chhattisgarh.